Economic Recovery Following the Covid-19 Pandemic in Indonesia with a Local Branding Strategy Leveraging Youth Participation in the Green-Creative Economy Digitization Program (PRO-DEKHA) - Fathul Jawad; Muhamad Fikri Asy'ari; Sahda Nabila Agusta; Ghina Hana Zafira; Aqmal Mei Shandika (West Science Interdisciplinary Studies, 2023)
The Covid-19 domino effect impacts both the health sector and the Indonesian economy. In 2020, there was a 2.07 percent economic decline compared to 2019 due to the prevention of an increasing number of Covid-19 spreads, which hampered economic activities and impacted social welfare felt by the community, one of which was Micro, Small, and Medium Enterprises (MSMEs). MSMEs contributed 61.97 percent of the national Gross Domestic Product (GDP) in 2020, indicating that MSMEs play an important role in the Indonesian economy. This raises awareness about the importance of creating a sustainable economy, which can be accomplished through economic digitization. Economic digitization uses the internet and artificial intelligence (AI) to facilitate economic activity. During the epidemic, one of the economic sectors that survived was the digital economy, for example, Shopee, Tokopedia, and others. Thus, economic digitalization assists the younger generation's 'green-creative economy.' Indonesian youth can leverage the digitalization of the green-creative economy to benefit the Indonesian economy as a whole. This article will address the issue of how youth can contribute to economic digitization by promoting local branding of local vegetables and fruits in a 'green-creative economy' to help Indonesia recover from the pandemic. This article aims to ascertain the role of youth in promoting economic digitization in Indonesia following the pandemic by strengthening local branding for the 'green-creative economy.' This relates to the Green Economic and Digital Economy concepts, which aim to enhance human well-being and sustainable green economic growth to improve environmental quality through digital technology. The paper uses qualitative research methodologies in conjunction with descriptive analysis research via a literature review. Thus, the community's Green-Creative Economic Digitization Program (PRO-DEKHA) aims to promote local branding of a 'green-creative economy' as a means of economic recovery by Indonesia's eighth Sustainable Development Goal (SDG) on decent work and economic growth.